Zirconium in the Nuclear Industry: Eleventh International Symposium 1996
DOI: 10.1520/stp16173s
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term In Situ Corrosion Investigation of Zr Alloys in Simulated PWR Environment by Electrochemical Measurements

Abstract: The corrosion behavior of Zircaloy-type alloys with different tin contents of 1.55, 0.70, and 0.55 wt% was studied at 350°C and 17 MPa in an environment similar to PWR primary water. For this non-interrupted test, a special autoclave system was used that was equipped with electrical feed that allowed followup on the growth of oxide layers by impedance spectroscopy and corrosion potential measurement at high temperature and pressure. As a reference electrode, a platinum wire was used that works as a hydrogen el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…For example, it has been previously proposed that periodicities observed in oxide structures were caused by the opening and closing operations of the autoclave to weigh samples rather than by the corrosion process itself. This is not the case in the current study, because the 360°C pure water samples were tested in the same autoclave with the same sample-weighing schedule and yet show vastly different periodicities, in agreement with prior results [31]. Because we examine bulk samples, with the oxide still attached to the metal, the artefacts related to relaxation of stress and consequent tetragonal destabilization due to dissolution of the underlying metal during sample preparation are minimized [1,2].…”
Section: Discussionsupporting
confidence: 84%
“…For example, it has been previously proposed that periodicities observed in oxide structures were caused by the opening and closing operations of the autoclave to weigh samples rather than by the corrosion process itself. This is not the case in the current study, because the 360°C pure water samples were tested in the same autoclave with the same sample-weighing schedule and yet show vastly different periodicities, in agreement with prior results [31]. Because we examine bulk samples, with the oxide still attached to the metal, the artefacts related to relaxation of stress and consequent tetragonal destabilization due to dissolution of the underlying metal during sample preparation are minimized [1,2].…”
Section: Discussionsupporting
confidence: 84%
“…The fraction of hydrogen produced during corrosion that is absorbed into the metal, is called the hydrogen pick-up fraction (HPUF) and varies with alloy composition. It has been demonstrated that alloys with a more electrically conductive oxide layer exhibit a lower HPUF [14]. This allows electrons to move more freely though the oxide and thus allows hydrogen ion/electron recombination to occur further from the metal/oxide interface, which consequently reduces the probability of the hydrogen reaching the cladding metal [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of electron transport is still unclear [24,25,28,29], it seems reasonable to consider that both bulk and localized conduction can contribute to the overall rate [29][30][31][32]. The preceding arguments indicate that oxide electronic conductivity is a key parameter in controlling zirconium alloy oxidation [33,34].…”
Section: Rate-limiting Step In Uniform Zirconium Alloy Corrosionmentioning
confidence: 99%
“…This can be explained by the doping effect of the donor Nb 5þ at the interface with the aqueous medium, which increases the electron concentration at the oxide-water interface, thereby promoting the hydrogen discharge process [26,44]. Electrochemical measurements have also shown that oxide electronic conductivity is increased by Nb additions, promoting hydrogen evolution at the oxide-water interface and reducing hydrogen uptake [34]. However, these effects cannot readily explain the observed variations of f i H as a function of exposure time [13].…”
Section: Hydrogen Pickup In Zirconium Alloysmentioning
confidence: 99%
See 1 more Smart Citation